2020
DOI: 10.1038/s41598-020-65259-8
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 generated Pompe knock-in murine model exhibits early-onset hypertrophic cardiomyopathy and skeletal muscle weakness

Abstract: Infantile-onset Pompe Disease (IOPD), caused by mutations in lysosomal acid alpha-glucosidase (Gaa), manifests rapidly progressive fatal cardiac and skeletal myopathy incompletely attenuated by synthetic GAA intravenous infusions. The currently available murine model does not fully simulate human IOPD, displaying skeletal myopathy with late-onset hypertrophic cardiomyopathy. Bearing a Cre-LoxP induced exonic disruption of the murine Gaa gene, this model is also not amenable to genome-editing based therapeutic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…A significant divergence of the model from human c.1935C>A IOPD is the lack of infantile mortality in KI mice. This KI mouse, along with the Gaa Em1826dupA KI mouse strain previously generated in our laboratory[15] and other previously published Gaa KO models [2426], all demonstrate null or nearly-zero GAA enzyme activity. Nevertheless, no neonatal mortality has been observed in any model, while neonatal death is the inevitable clinical outcome in untreated IOPD patients[27, 28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant divergence of the model from human c.1935C>A IOPD is the lack of infantile mortality in KI mice. This KI mouse, along with the Gaa Em1826dupA KI mouse strain previously generated in our laboratory[15] and other previously published Gaa KO models [2426], all demonstrate null or nearly-zero GAA enzyme activity. Nevertheless, no neonatal mortality has been observed in any model, while neonatal death is the inevitable clinical outcome in untreated IOPD patients[27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Gaa c.1935 gRNA-2 demonstrated higher on-target editing (26.7±10.7%) and HDR efficiency (5.4±3.4%) than gRNA-1 (on-target editing: 13.2±3.7%; HDR efficiency: 3.8±0.6%) (Table 1). Given our prior success in generating Gaa Em1826dupA KI cell and transgenic mouse lines using a dual overlapping gRNA strategy [15], we applied this same method towards the generation of Gaa c.1935C>A KI C2C12 cells and Gaa Em1935C>A mice.…”
Section: Gaa C1935 Target Locus Guide Rna and Donor Ssodn Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the availability of CRISPR tools to generate novel mouse models that better recapitulate human disease phenotypes could help accelerate the design of the next generation of PD therapies. Huang et al recently reported the generation of a novel murine IOPD model utilizing dual sgRNA CRISPR-Cas9 homology-directed recombination to harbor the orthologous Gaa mutation c.1826dupA (p.Y609 *) [ 161 ]. This model effectively recapitulated the patient-specific genotype, which results in hypertrophic cardiomyopathy and skeletal muscle weakness, hallmarks of human IOPD.…”
Section: Gene Therapy For Pompe Diseasementioning
confidence: 99%
“…Finally, the Gaa c.1826dupA mouse model was generated using the novel CRISPR-Cas9 homology-directed recombination to harbor the orthologous Gaa mutation c.1826dupA (p.Y609*), which causes human IOPD [ 245 ]. These mice showed a major decrease in GAA activity (>95% in heart, diaphragm and gastrocnemius), massive increases in glycogen content (185 and 28 fold increases in the heart and gastrocnemius, respectively), autophagy impairment, decreased forelimb muscle strength, significant reduction in body mass and abnormal cardiac function [ 245 ].…”
Section: Glycogen Storage Diseasesmentioning
confidence: 99%